Exercise by the health advocacy nurse in patient defense: integrative review (Research, Society and Development, 2021)
The term health advocacy by nursing is defined as the active support of nurses in relation to the patient's rights and choices, as well as clarifying their healthcare decisions with assistance in choosing informed decisions and protecting human rights. The aim of this article is to analyze, in the national and international literature, the practice of health advocacy in patient defense by nurses. This is an integrative review conducted from March to July 2021 through the search for studies published from 2010 to 2020 in journals indexed in PubMed/MEDLINE, LILACS and CINAHL. The sample consisted of fourteen primary studies, mainly in English and conducted in Brazil, USA, Australia, Sweden, Iran and Japan. The articles that made up the study sample can be systematized and presented from the categories "Identification of vulnerabilities of law of the patient” and “Communication with patients, family members and other professionals”. The nurses are advocating against actions that can be characterized as identification, communication to defend the patient's rights and facing barriers. a clearer definition of health advocacy by nurses is essential, as well as more studies analyzing the practice of exercise.